A critical discourse analysis of beauty product advertisements / Kuldip Kaur Maktiar Singh, Norimah Mohamad Yunus and Nalini Arumugam - Kuldip Kaur Maktiar Singh; Mohamad Yunus, Norimah; Nalini Arumugam (Research Management Institute (RMI), 2012)
Women's magazines are occupied with advertisements of various beauty products which regularly reach a vast number of women. The influence of advertisements in this print media has led the beauty product companies to employ various strategies to attract and convince consumers. This study examined beauty advertisements in local English magazines from a Critical Discourse Analysis perspective. This study mainly focused on the use of language in beauty advertisements and strategies employed by advertisers to manipulate and influence their customers. The analysis is based on Fairclough's three-dimensional framework. It demonstrates how the ideology of 'beauty' is produced and reproduced through advertisements in popular local women's magazines. A qualitative research was conducted on beauty product advertisements in two popular local women's magazines, Cleo and Women's Weekly.The findings indicated that advertisers used various strategies to manipulate women. The advertisements promote an idealised lifestyle and manipulate readers to a certain extent into believing whatever that is advertised is indeed true. This study demonstrates how the ideology of beauty is constructed and reconstructed through magazines by stereotyping how beauty products are synonymous with a better life. Advertising language is used to control people's minds. Thus people in power (advertisers) use language as a means to exercise control over others.